Stock-recruitment-environment relationships of invertebrate resources in Western Australia and their link to pro-active management harvest strategies. (November 2021) - Caputi, Nick; Chandrapavan, Arani; Kangas, Mervi; de Lestang, Simon; Hart, Anthony; Johnston, Danielle; Penn, James
Abstract: There are several ways to set biological reference points (BRP) for harvest strategies, but one of the most direct methods is to use the stock-recruitment relationship (SRR). Even if the SRR is not statistically significant, it provides valuable information about the spawning stock levels that don't influence the recruitment that is relevant to setting BRP. Environmental factors, particularly extreme events such as the 2011 Western Australia (WA) marine heatwave, are typically a major driver of recruitment, so it is important to assess their influence as ignoring this effect may bias the SRR. This study examines the SRR for 13 invertebrate stocks in WA including lobster, prawn, scallop, abalone, pearl oysters and crabs. These stocks have long time series of fishery-independent juvenile abundance indices, which provide a clear signal of the year-class strength that improves the ability to assess the SRR and environmental effects. Eleven stocks showed a significant environmental effect on recruitment with seven stocks demonstrating a significant spawning stock effect. The stock-recruitment data is used to determine the BRP based on the species' specific biological information, even when the relationship is not significant. Importantly, management action in the harvest control rules is not just reactive to low spawning stock levels but is proactive based on the juvenile abundance to ensure that the level of fishing results in future spawning stocks being maintained above the BRP. This evidence-based approach to setting BRPs and the proactive management approach adopted in the harvest strategy can be invaluable to fisheries management generally.